Opendoor laminoplasty is good Surgical treatment for multilevel cervical spinal canal stenosis (TAJ: Journal of Teachers Association, 2018)
Background : Expansive open-door laminoplasty is widely accepted as a reliable procedure for cervical myelopathy. However, one acknowledged complication is spring-back complication or closure of the door which may result in re-stenosis of cervical canal and neurologic deterioration. The study aimed for addressing our cervical open-door laminoplasty technique with plate and screw and subsequently the follow-up outcomes.Methods: Thirty consecutive patients who underwent open-door laminoplasty with the novel technique were included and followed for minimum 5 years from July 2011 to June 2016. Antero-posterior diameter (APD) of the vertebral canal of C4 was measured in lateral cervical radiographs. Neurologic scenarios were assessed using the Japanese Orthopaedic Association (JOA) scores.Results: Twenty-five males (83.3%) and five (16.7%) females with an average follow-up of 68 months were enrolled. The preoperative APD was 13.22 mm (±1.15), whereas the postoperative APD increased to 31.23 mm (±2.43) with an expansion ratio of 136.23% (P < 0.05). The JOA score increased from 8.5 preoperatively to 13.45 postoperatively with a recovery rate of 58.2% (P < 0.05). The elevated laminas were maintained open during the follow-up period.Conclusions: Our technique with plate and screw for laminoplasty is a simple and efficient method for maintaining the decompression of cervical canal and neurologic improvement.TAJ 2016; 29(1): 33-38